Porosity-induced emission: exploring color-controllable fluorescence of porous organic polymers and their chemical sensing applications. Issue 26 (10th June 2015) - Li, Yankai; Bi, Shiming; Liu, Fei; Wu, Shengying; Hu, Jun; Wang, Limin; Liu, Honglai; Hu, Ying
Abstract : "Porosity-induced emission" for the synthesis of POPs with tunable fluorescence color for chemical sensing applications. Abstract : Most organic dyes dissipate their excitation energy in the aggregated state because of the "aggregation-caused quenching" effect, deteriorating their application in optoelectronic devices. To prevent the "aggregation-caused quenching" effect, we incorporate a dye-based fluorophore into a porous organic polymer skeleton because porosity would allow the spatial isolation of fluorophores to maintain their emission. Tuning the fraction of fluorophores in the skeleton of FL-SNW-DPPs could spread the emission color coverage from red to blue in both solid-state and suspension. More importantly, the combination of fluorescence and porosity of FL-SNW-DPPs would provide more space to transduce the molecular interaction between adsorbed analytes and fluorophores to the detectable changes in light emission, leading to the fluorescence-off or fluorescence-on detection of electron-deficient or electron-rich analytes.